Controversial points in the surgical treatment of gallbladder cancer with delayed diagnoses - LE Sen, ZUO Yue, DENG Zhengdong, WANG Jianming (Waike lilun yu shijian, 2025)
Gallbladder cancer with delayed diagnoses, as a malignant tumor diagnosed intraoperatively or postoperatively incidentally in benign gallbladder diseases, radical surgical treatment is its core treatment, and the necessity of re-operation, timing of surgery, choice of surgical procedure, definition of resection extent, and preoperative neoadjuvant therapy still remain controversial. Re-operation for gallbladder cancer with delayed diagnoses needs to balance tumor radicalization, postoperative risk, and survival benefit, and combining neoadjuvant therapy to facilitate radical treatment, and develop individualized protocols. The multidisciplinary team should integrate innovative technologies and multi-center prospective studies to promote the development of precise treatment strategies for gallbladder cancer with delayed diagnoses and optimize the survival of patients.